The Influence of Financial Ratios on Financial Distress: An Empirical Study of Banks Listed on the Indonesia Stock Exchange - Ardhan Ardiansyah Kawakibi; Mohamad Yusuf Kurniawan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of financial ratios on financial distress conditions in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. The independent variables in this study include the liquidity ratio (Current Ratio), the solvency ratio (Debt to Assets Ratio), the profitability ratio (Return on Equity), and the activity ratio (Total Assets Turnover), while the dependent variable is financial distress measured using a dummy variable. The sampling method uses a non-probability sampling approach with a purposive sampling technique, resulting in 20 banking companies that meet the research criteria. Data analysis was carried out using the logistic regression method to test the extent to which the probability of financial distress can be predicted through the financial ratios used. The results show that the Current Ratio, Debt to Assets Ratio, Return on Equity, and Total Assets Turnover do not have a significant effect on financial distress conditions in banking companies in Indonesia. This finding indicates that traditional financial ratios have not been able to effectively detect potential financial difficulties in the banking sector which has special characteristics in capital structure and asset management. This research is expected to be a reference for researchers and practitioners in developing a more comprehensive financial distress prediction model in the future.